Corrosion Behavior of Zinc-Graphite Metal Matrix Composite in 1 M of HCl. (9th March 2014) - Afifi, M. A.
Abstract : This paper is aimed at investigating the corrosion behavior of Pure and Zinc-graphite particles with percentage of 1, 3, and 5%, respectively. The composites were fabricated by powder metallurgy method. Corrosion tests were performed according to ASTM standard. Corrosion rate was calculated and it is found that in all cases the corrosion rate was decreasing with the increase in exposure time. Meanwhile, the microstructure of composites was imaged and analyzed using optical microscope and scanning electron microscope. It is observed that the best corrosion resistance was zinc with 1% Graphite while Zinc with 3% and 5% Graphite composites did not enhance the corrosion resistance comparing to pure Zinc.